Preparation method and application of glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel
The use of glycyrrhizic acid/carbon nanoenzyme injectable antibacterial hydrogels combined with photothermal-drug synergistic treatment with near-infrared light irradiation, solves the problems of antibiotic resistance and slow drug efficacy, and achieves the wounds of multiple bacterial infections Efficient healing.
Patent Information
- Application Number
- CN202410545570.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-05-06
AI Technical Summary
Existing antibiotics have drug resistance problems in treating bacterial infection wounds, and the effect of a single drug-loaded hydrogel is slow, making it difficult to effectively promote the healing of multiple bacterial infection wounds.
The antibacterial hydrogel can be injected with glycyrrhizic acid/carbon nanoenzyme, which wraps carbon nanoenzyme nanoparticles through chitosan, and is loaded with glycyrrhizic acid, an active ingredient for medicinal plants, combined with the photothermal and drug synergistic treatment effect under near-infrared light. Simulate the activities of SOD enzymes and CAT enzymes to clear ROS and relieve inflammation.
The synergistic antibacterial and anti-inflammatory effects on a variety of bacteria have been achieved, the use of antibacterial drugs has been reduced, the generation of drug resistance has been avoided, and the healing of bacterial infection wounds has been significantly promoted.
Smart Images

Figure CN118403005B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical technology, and in particular relates to a preparation method and application of a glycyrrhizic acid / carbon nanoenzyme injectable antibacterial hydrogel. Background Art
[0002] Injectable hydrogels have the unique feature of being able to fill defects of any appearance without the need for surgery, and they exhibit low viscosity properties in the sol state. They can also be easily adjusted to the desired shape to meet the needs. Due to the unique advantages of in situ drug delivery and good injectability, injectable hydrogels have attracted considerable attention as carriers for local and sustained drug delivery. Compared with preformed hydrogels that need to be surgically implanted in the body, in situ injectable hydrogels have the advantages of being non-invasive and having adjustable in situ formed hydrogel geometry. With the development of the medical field, injectable hydrogel systems as a drug delivery carrier have attracted more and more attention from researchers due to their advantages such as easy application, increased local drug concentration, prolonged drug retention time, and good biocompatibility.
[0003] Compared with other drug preparations, hydrogels have a higher specific surface area and high porosity, which helps cells attach and load drugs. In addition, studies have shown that the activity of drugs will not be destroyed during the preparation of hydrogels. In existing literature reports, most of the drugs loaded in hydrogel drug delivery systems are antibiotics.
[0004] Although the use of antibiotics has promoted wound healing to a certain extent, there are still many disadvantages. Due to severe bacterial infection, wounds are often colonized by multiple bacteria, and bacterial cross-infection can lead to bacterial colony effects, which can lead to strong resistance to antibiotics; in addition, its production seriously affects the efficacy of antibiotics. Therefore, it is necessary to find a multifunctional hydrogel dressing as an alternative to antibiotics, and to use non-antibiotic treatment methods to achieve efficient antibacterial and anti-inflammatory effects, which is crucial for the successful treatment of bacterially infected wounds. Summary of the invention
[0005] To solve the above technical problems, the present invention proposes a preparation method and application of a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel (CGA hydrogel). The injectable antibacterial hydrogel of the present invention is a composite hydrogel, which uses chitosan as a polymer skeleton to wrap carbon nanozyme nanoparticles, and loads glycyrrhizic acid, an active ingredient of medicinal plants, to obtain a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel. The injectable performance of the hydrogel can completely fill wounds of complex shapes and is easy to administer at the wound site. In addition, the hydrogel can generate heat under near-infrared light irradiation and promote the release of glycyrrhizic acid, thereby achieving a photothermal-drug synergistic therapeutic effect on a variety of bacteria. At the same time, the carbon nanozyme in this glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel can simulate the activity of SOD enzymes and CAT enzymes, remove ROS, effectively relieve inflammation, and promote the healing of wounds infected with multiple bacteria. Through the above synergistic antibacterial and anti-inflammatory effects, the purpose of reducing medication and increasing efficacy can be achieved, and the healing of wounds infected with multiple bacteria can be effectively promoted.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel comprises the following steps:
[0009] Dispersing the carbon nanozyme in an acetic acid solution, performing ultrasonic dispersion, and adding chitosan to obtain a first solution;
[0010] Adding glycyrrhizic acid to the first solution and stirring evenly to obtain a second solution;
[0011] dissolving the temperature sensitive agent in water to obtain a third solution;
[0012] The second solution and the third solution are mixed and stirred evenly to obtain a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel.
[0013] Furthermore, the preparation method of the carbon nanozyme is as follows:
[0014] Mix dimethylimidazole and methanol to obtain solution A;
[0015] Mixing zinc nitrate hexahydrate with methanol to obtain solution B;
[0016] Add the solution B into the solution A and stir evenly;
[0017] The supernatant was discarded after centrifugation, and methanol was added to make the liquid level higher than the obtained solid. Ultrasonic dissolution was performed until there was no precipitation, and then centrifugation was performed again. This was one washing. After washing three times, the supernatant was discarded, vacuum dried, and then the obtained solid was ground and calcined to obtain the carbon nanozyme.
[0018] Furthermore, in the preparation method of the carbon nanozyme, the mass volume ratio of the dimethylimidazole to methanol is 3.24 g: 100 mL;
[0019] The mass volume ratio of the zinc nitrate hexahydrate to methanol is 2.94 g:100 mL;
[0020] The speed of each centrifugation was 12000 rpm, and the time of each centrifugation was 10 min;
[0021] The calcination temperature is 900° C., and the calcination time is 3 h.
[0022] Furthermore, the preparation method of carbon nanozyme is as follows:
[0023] Weigh 3.24g of dimethylimidazole, add 100mL of methanol and put it into a round-bottom flask to obtain solution A; weigh 2.94g of zinc nitrate hexahydrate, add 100mL of methanol and put it into a beaker to obtain solution B; after the solution B and the solution A are fully stirred, add the solution B to the solution A and continue stirring for 5h until it is uniform; centrifuge the mixed solution (12000rpm, 10min) and discard the supernatant, then add methanol to make its liquid level higher than the obtained solid, ultrasonically dissolve until there is no precipitation and centrifuge again (12000rpm, 10min), this is one cleaning, discard the supernatant after washing 3 times, vacuum dry at 80℃ for 12h, grind the obtained solid after drying, and calcine it in a tubular furnace (900℃, 3h) to obtain carbon nanozyme.
[0024] Furthermore, the volume ratio of the second solution to the third solution is (3-10):1.
[0025] Furthermore, the volume ratio of the second solution to the third solution is 3:1, 5:1 or 10:1.
[0026] Furthermore, the temperature sensitive agent is disodium β-glycerophosphate pentahydrate.
[0027] Furthermore, the preparation method of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel is as follows:
[0028] Dispersing the carbon nanozyme in a 0.1 M acetic acid solution, dispersing it evenly by ultrasound, adding chitosan and stirring for 2-5 hours to prepare a first solution, wherein the concentration of chitosan in the first solution is 20-30 mg / mL;
[0029] Adding glycyrrhizic acid to the first solution and stirring thoroughly until uniform to obtain a second solution, wherein the concentration of glycyrrhizic acid in the second solution is 0.5-2 mg / mL;
[0030] Dissolving the thermosensitive agent β-glycerophosphate disodium pentahydrate in ultrapure water to obtain a third solution, wherein the concentration of the third solution is 0.5-2 g / mL;
[0031] The second solution and the third solution were mixed in different volume ratios (3:1, 5:1 or 10:1), stirred at 4°C until uniform, and finally the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel was obtained at 37°C.
[0032] The present invention uses non-antibiotic drug glycyrrhizic acid as an antibacterial agent, carbon nanozyme as a photothermal agent, and utilizes the simulated enzyme action of carbon nanozyme to remove ROS, reduce inflammatory response, thereby promoting wound healing, and loads glycyrrhizic acid and carbon nanozyme into hydrogel to prepare a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel (CGA hydrogel). The present invention uses a two-phase synthesis method to construct a thermosensitive hydrogel with excellent properties, uses an in-situ coating method to load glycyrrhizic acid, modifies the carbon nanozyme on the surface of the hydrogel, and gives it the ability of antibacterial and anti-inflammatory effects; through the regulation of near-infrared light, the hydrogel exerts a drug-photothermal synergistic antibacterial effect, avoiding the problem of drug resistance caused by excessive use of antibacterial drugs; the hydrogel of the present invention has injectable performance, can completely fill wounds of complex shapes, and is easy to administer at the wound site; the carbon nanozyme in the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel can simulate the activity of SOD enzymes and CAT enzymes, remove ROS, effectively relieve inflammation, and promote the healing of wounds infected with multiple bacteria.
[0033] The second technical solution of the present invention:
[0034] A glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared according to the above preparation method.
[0035] The third technical solution of the present invention:
[0036] The application of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel in the preparation of antibacterial drugs.
[0037] The fourth technical solution of the present invention:
[0038] The glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel is used in the preparation of a drug for promoting the healing of wounds infected with multiple bacteria.
[0039] Compared with the prior art, the present invention has the following advantages and technical effects:
[0040] ① The glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel of the present invention has a significant antibacterial effect due to the addition of glycyrrhizic acid in the production of the hydrogel. At the same time, the production method is simple, the process conditions are mild, and conventional equipment can be used for preparation. However, the drug dosage required for a single drug-loaded hydrogel is large and the drug effect is slow, and it needs to work in synergy with other antibacterial substances to obtain better therapeutic effects.
[0041] ② The carbon nanozyme in the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel component of the present invention acts as a photothermal agent, which can convert light energy into thermal energy, causing physical damage (thermal destruction) to bacteria and killing microorganisms, and produces a photothermal-drug synergistic antibacterial effect with glycyrrhizic acid, thus avoiding the problem of drug resistance caused by excessive use of antibacterial drugs.
[0042] ③ The carbon nanozyme in the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel component of the present invention can remove ROS by simulating the activity of SOD enzyme and CAT enzyme, and can effectively remove inflammation, thereby promoting wound healing.
[0043] ④ The injectable property of the hydrogel in the present invention can completely fill wounds of complex shapes and is easy to administer at the wound site.
[0044] ⑤ In the present invention, the amount of drug released increases under near-infrared laser irradiation, and a small amount of drug is continuously released after the near-infrared laser irradiation is turned off. It can be seen that near-infrared laser irradiation can be used as a "switch" to achieve the controllable release of glycyrrhizic acid in the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel, that is, near-infrared light can achieve the controlled release of glycyrrhizic acid while synergistically enhancing the antibacterial effect of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel.
[0045] In summary, the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel of the present invention has excellent photothermal, antibacterial and anti-inflammatory properties, and has great development and application prospects as a wound dressing. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0047] Figure 1 This is a picture of the multiple forms (matrix not gelled, matrix gelled, drug-loaded not gelled, and drug-loaded gelled) of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1;
[0048] Figure 2 This is a multi-morphological picture of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1;
[0049] Figure 3 This is a scanning electron microscope image of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1;
[0050] Figure 4 This is the infrared spectrum of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1;
[0051] Figure 5The activity diagram of SOD-like enzyme and CAT-like enzyme of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1;
[0052] Figure 6 This is the temperature change curve of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 under 808nm near-infrared laser irradiation;
[0053] Figure 7 The glycyrrhizic acid release curves of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 in the near-infrared light irradiation group (NIR(+)) and the non-near-infrared light irradiation group (NIR(-));
[0054] Figure 8 This is a bacterial plate coating image of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 after different treatments for 12 hours;
[0055] Fig. 9 This is a graph showing the healing rate of mouse infected wounds of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1. DETAILED DESCRIPTION
[0056] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0057] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0058] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0059] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0060] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0061] All raw materials used in the examples of the present invention are commercially available.
[0062] The preparation method of the carbon nanozyme in the embodiment of the present invention is as follows: weigh 3.24g of dimethylimidazole, add 100mL of methanol and put it into a round-bottom flask to obtain solution A; weigh 2.94g of zinc nitrate hexahydrate, add 100mL of methanol and put it into a beaker to obtain solution B; after the solution B and the solution A are fully stirred, the solution B is added to the solution A and continued to stir for 5h; the mixed solution is centrifuged (12000rpm, 10min) and the supernatant is discarded, and methanol is added to make its liquid level higher than the obtained solid, ultrasonically dissolve until there is no precipitation and centrifuge again (12000rpm, 10min), this is one cleaning, and the supernatant is discarded after washing 3 times, and vacuum dried at 80°C for 12h. After drying, the obtained solid is ground and crushed, and calcined in a tubular furnace (900°C, 3h) to obtain the carbon nanozyme.
[0063] The technical solution of the present invention is further illustrated by the following embodiments.
[0064] Example 1
[0065] 3.3 mg of carbon nanozyme was dispersed in 0.1 M acetic acid solution, and ultrasonication was used to make it uniformly dispersed. Chitosan was added and stirred for 5 hours to prepare a first solution. The concentration of chitosan in the first solution was 20 mg / mL, and the concentration of carbon nanozyme in the first solution was 300 μg / mL;
[0066] Add glycyrrhizic acid to the first solution and stir thoroughly until uniform to obtain a second solution, wherein the concentration of glycyrrhizic acid in the second solution is 1 mg / mL;
[0067] Dissolving the thermosensitive agent β-glycerophosphate disodium pentahydrate in ultrapure water to obtain a third solution with a concentration of 1 g / mL;
[0068] The second solution and the third solution were mixed in a volume ratio of 10:1, stirred at 4°C until uniform, and finally, glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel was obtained at 37°C, which was recorded as CS-β / C / GA.
[0069] Comparative Example 1 Hydrogel group without glycyrrhizic acid and carbon nanozyme loading (CS-β)
[0070] Add chitosan to a 0.1 M acetic acid solution and stir for 5 hours to prepare a first solution, wherein the concentration of chitosan in the first solution is 20 mg / mL;
[0071] Dissolving the thermosensitive agent β-glycerophosphate disodium pentahydrate in ultrapure water to obtain a second solution with a concentration of 1 g / mL;
[0072] The first solution and the second solution were mixed in a volume ratio of 10:1, stirred at 4°C until uniform, and finally a hydrogel group (CS-β) without glycyrrhizic acid and carbon nanozyme loading was obtained at 37°C.
[0073] Comparative Example 2 Hydrogel group without glycyrrhizic acid loaded with carbon nanozyme (CS-β / C)
[0074] 3.3 mg of carbon nanozyme was dispersed in 0.1 M acetic acid solution, and ultrasonication was used to make it uniformly dispersed. Chitosan was added and stirred for 5 hours to prepare a first solution. The concentration of chitosan in the first solution was 20 mg / mL, and the concentration of carbon nanozyme in the first solution was 300 μg / mL;
[0075] Dissolving the thermosensitive agent β-glycerophosphate disodium pentahydrate in ultrapure water to obtain a second solution with a concentration of 1 g / mL;
[0076] The first solution and the second solution were mixed in a volume ratio of 10:1, stirred at 4°C until uniform, and finally a hydrogel group (CS-β / C) without glycyrrhizic acid loaded and introduced with carbon nanozyme was obtained at 37°C.
[0077] Figure 1 The pictures are of the multiple forms of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 (matrix group (matrix group, i.e., CS-β group) not gelled, matrix gelled, drug-loaded group (drug-loaded group, i.e., CS-β / C / GA group) not gelled, and drug-loaded gelled). The non-gelled state is in a flowable state, and the gelled state can be observed in a 37°C water bath; Figure 2 This is a multi-morphological picture of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1. Figure 1 and Figure 2 It can be seen that the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel of the present invention has various forms.
[0078] Figure 3 This is a scanning electron microscope image of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1. Figure 4The infrared spectrum of the graph is shown in Figure 1, wherein CS-β / C / GA is an injectable antibacterial hydrogel group with glycyrrhizic acid / carbon nanozyme (Example 1); CS-β / C is a hydrogel group with carbon nanozyme but not loaded with glycyrrhizic acid; CS-β is a hydrogel group without glycyrrhizic acid and carbon nanozyme; GA is a glycyrrhizic acid group; CS is a hydrogel group; β-GP is a disodium β-glycerophosphate pentahydrate group; Figure 3-4 It can be seen that CS-β / C / GA hydrogel was successfully prepared and glycyrrhizic acid and carbon nanozyme were successfully loaded.
[0079] Figure 5 The SOD-like enzyme and CAT-like enzyme activity diagram of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1. It can be seen that the scavenging rate of the hydrogel for superoxide anions is about 70%, proving that the hydrogel has a strong SOD-like enzyme activity; the O2 release in the hydrogel system is about 46 mg / L, which shows that the prepared hydrogel has a strong CAT-like enzyme activity and can catalyze the decomposition of H2O2.
[0080] Figure 6 The temperature change curve of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 under 808nm near-infrared laser irradiation. It can be seen that when the carbon nanozyme concentration is 300μg / mL, the temperature can reach 46.3°C within 3 minutes. The temperature of the solution in the control group hardly changed under light irradiation. When the carbon nanozyme concentration is 200μg / mL, the temperature reaches 41.6°C within 3 minutes. When the carbon nanozyme concentration is 400μg / mL, the temperature reaches 54.2°C. Therefore, the hydrogel with a carbon nanozyme concentration of 300μg / mL was selected for the next experiment, indicating that this glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel can be used as a photothermal material.
[0081] Figure 7 The glycyrrhizic acid release curves of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 are shown in the near-infrared light irradiation group (NIR(+)) and the non-near-infrared light irradiation group (NIR(-)). It can be seen that under the irradiation of the near-infrared laser, the amount of glycyrrhizic acid released from the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel increases, and after the irradiation is stopped, the amount of glycyrrhizic acid released decreases. This shows that near-infrared light can act as a "switch" to remotely control the release of glycyrrhizic acid.
[0082] The plate coating method was used to evaluate the in vitro antibacterial ability of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel. Before the experiment, all samples and facilities related to this experiment were irradiated under ultraviolet light for more than 30 minutes to disinfect and sterilize.
[0083] ①Eight groups of experimental subjects were set up respectively: control group (untreated, Control), control group under near-infrared laser irradiation (Control+NIR), hydrogel group without glycyrrhizic acid and carbon nanozyme load (CS-β), hydrogel group without glycyrrhizic acid and carbon nanozyme load under near-infrared laser irradiation (CS-β+NIR), hydrogel group without glycyrrhizic acid load and carbon nanozyme introduced (CS-β / C), hydrogel group without glycyrrhizic acid load and carbon nanozyme introduced under near-infrared laser irradiation (CS-β / C+NIR), injectable antibacterial hydrogel group with glycyrrhizic acid / carbon nanozyme introduced (CS-β / C / GA), injectable antibacterial hydrogel group with glycyrrhizic acid / carbon nanozyme introduced under near-infrared laser irradiation (CS-β / C / GA+NIR). The above eight groups are recorded as I-VIII respectively.
[0084] Among them, the control group specifically refers to a normally cultured bacterial group that has not undergone any treatment; the wavelength of the near-infrared laser irradiation is 808nm, and the time is 3min.
[0085] ②Put the gelled block of glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel into 1mL10 5 CFU / mL of methicillin-resistant Staphylococcus aureus or Pseudomonas aeruginosa suspension was placed in a microcentrifuge tube and reacted for 1 hour.
[0086] ③ Use a pipette to draw 100 μL and use a spreader to evenly apply it on the agar plate until the water stain disappears. Place it in a 37℃ constant temperature incubator and incubate it for 12 hours. Repeat each group of experiments three times and correct the experimental results. Compare the antibacterial activity by comparing the number of colonies.
[0087] Figure 8The following is a bacterial plate coating diagram of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 after different treatments for 12 hours. The colony count of methicillin-resistant Staphylococcus aureus (MRSA) treated with the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group (i.e., CS-β / C / GA group) was reduced by 74.81% compared with the control group, and the colony count of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group treated with near-infrared laser irradiation (i.e., CS-β / C / GA+NIR group) was reduced by 99.08% compared with the control group; the colony count of MRSA treated with the CS-β group was reduced by 12.51% compared with the control group, the colony count of MRSA treated with the CS-β+NIR group was reduced by 12.98% compared with the control group, the colony count of MRSA treated with the CS-β / C group was reduced by 46.05% compared with the control group, and the colony count of MRSA treated with the CS-β / C+NIR group was reduced by 99.08% compared with the control group. 63.63%; the colony count of Pseudomonas aeruginosa (PA) treated with CS-β / C / GA group decreased by 66.67% compared with the control group, the colony count of CS-β / C / GA+NIR group decreased by 96.85% compared with the control group, the colony count of PA treated with CS-β group decreased by 14.17% compared with the control group, the colony count of PA treated with CS-β+NIR group decreased by 15.03% compared with the control group, the colony count of PA treated with CS-β / C group decreased by 31.23% compared with the control group, and the colony count of PA treated with CS-β / C+NIR group decreased by 59.06% compared with the control group (Note: In the above conclusion, there is no obvious difference in the number of colonies between the Control group and the Control+NIR group, so they can be compared at the same time and collectively referred to as the control group). It can be seen that the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel of the present invention exhibits a very significant synergistic antibacterial effect on both bacteria.
[0088] Xia Zhao et al. dissolved glycyrrhizic acid (1.3 mg / mL) in PBS to form a stable hydrogel at 37°C, which had a strong antibacterial rate against Staphylococcus aureus, but had no obvious antibacterial effect on Escherichia coli. The ferrous-induced glycyrrhizic acid (5.0 mg / ml) hydrogel prepared by Xu Ze et al. had high antibacterial ability against both Staphylococcus aureus and Escherichia coli. The glycyrrhizic acid concentration loaded by the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1 was 1 mg / ml, which showed a very significant antibacterial effect on both MRSA bacteria and PA bacteria, confirming its effect of reducing drugs and increasing efficacy.
[0089] By constructing a complex infection live mouse model, the healing rate of mouse infected wounds treated with glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel was systematically investigated.
[0090] The animal room conditions of Kunming female mice (weighing about 20g) used in the experiment were: temperature 24±1℃, humidity 50±10%. After a skin wound was constructed on the back of each mouse, 0.1mL of bacterial suspension (OD value of 1) was used for infection treatment. One day after infection, the mice were randomly divided into 8 groups, namely the control group (untreated Control), the control group under near-infrared laser irradiation (Control+NIR), the hydrogel group without glycyrrhizic acid and carbon nanozyme (CS-β), the hydrogel group without glycyrrhizic acid and carbon nanozyme under near-infrared laser irradiation (CS-β+NIR), the hydrogel group without glycyrrhizic acid loaded with carbon nanozyme (CS-β / C), the hydrogel group without glycyrrhizic acid loaded with carbon nanozyme under near-infrared laser irradiation (CS-β / C+NIR), the group of injectable antibacterial hydrogel with glycyrrhizic acid / carbon nanozyme (CS-β / C / GA), and the group of injectable antibacterial hydrogel with glycyrrhizic acid / carbon nanozyme under near-infrared laser irradiation (CS-β / C / GA+NIR). The wounds of the mice were recorded daily using a camera.
[0091] Fig. 9 The figure is a graph of the wound healing rate of mice infected with the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel prepared in Example 1. It can be seen that on the 4th day, the wound healing speed of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group treated with near-infrared laser irradiation was significantly faster than that of the control group and the no-light group. The average wound healing rate of the CS-β / C / GA+NIR group was 65%, and the average wound healing rates of the Control+NIR group and CS-β / C / GA were 48% and 61%; on the 10th day, the wound of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group treated with near-infrared laser irradiation was almost completely closed, which was significantly different from the other groups. The average wound healing rate of the CS-β / C / GA+NIR group was 95%, and the average wound healing rates of the Control+NIR group and CS-β / C / GA were 67% and 83%, showing a very significant photothermal synergistic antibacterial and anti-inflammatory effect.
[0092] Example 2
[0093] 3.0 mg of carbon nanozyme was dispersed in 0.1 M acetic acid solution, and ultrasonicated to make it evenly dispersed. Chitosan was added and stirred for 4 hours to prepare a first solution. The concentration of chitosan in the first solution was 25 mg / mL.
[0094] Add glycyrrhizic acid to the first solution and stir thoroughly until uniform to obtain a second solution, wherein the concentration of glycyrrhizic acid in the second solution is 0.5 mg / mL;
[0095] Dissolving the thermosensitive agent β-glycerophosphate disodium pentahydrate in ultrapure water to obtain a third solution with a concentration of 0.5 g / mL;
[0096] The second solution and the third solution were mixed in a volume ratio of 5:1, stirred at 4°C until uniform, and finally the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel was obtained at 37°C.
[0097] The plate coating method was used to evaluate the in vitro antibacterial ability of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel. The specific experimental process is the same as Example 1. The antibacterial activity was compared by comparing the number of colonies. The number of methicillin-resistant Staphylococcus aureus colonies in the CS-β / C / GA group was reduced by 68.83% compared with the Control group, the number of colonies in the CS-β / C / GA+NIR group was reduced by 91.03% compared with the Control+NIR group, the number of MRSA colonies in the CS-β group was reduced by 10.21% compared with the control group, the number of MRSA colonies in the CS-β+NIR group was reduced by 10.93% compared with the control group, the number of MRSA colonies in the CS-β / C group was reduced by 42.38% compared with the control group, and the number of MRSA colonies in the CS-β / C+NIR group was reduced compared with the control group. 58.43%; the number of Pseudomonas aeruginosa colonies in the CS-β / C / GA group was reduced by 84.34% compared with the Control group, the number of colonies in the CS-β / C / GA+NIR group was reduced by 95.72% compared with the Control+NIR group, the number of PA colonies in the CS-β group was reduced by 11.86% compared with the control group, the number of PA colonies in the CS-β+NIR group was reduced by 11.98% compared with the control group, the number of PA colonies in the CS-β / C group was reduced by 29.42% compared with the control group, and the number of PA colonies in the CS-β / C+NIR group was reduced by 53.26% compared with the control group. It can be seen that the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel of the present invention exhibits a very significant synergistic antibacterial effect on both bacteria.
[0098] By constructing a complex infection live mouse model, the wound healing rate of mice infected with glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel was systematically investigated. The specific experimental process is the same as Example 1. On the 4th day, the wound healing speed of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group treated with near-infrared laser irradiation was faster than that of the control group and the no-light group. The average wound healing rate of the CS-β / C / GA+NIR group was 61%, and the average wound healing rates of the Control+NIR group and CS-β / C / GA were 43% and 58%; on the 10th day, the wound of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group treated with near-infrared laser irradiation was almost completely closed, which was significantly different from the other groups. The average wound healing rate of the CS-β / C / GA+NIR group was 92%, and the average wound healing rate of the Control+NIR group and CS-β / C / GA was 64% and 79%, showing a good photothermal synergistic antibacterial and anti-inflammatory effect.
[0099] Example 3
[0100] 2.7 mg of carbon nanozyme was dispersed in 0.1 M acetic acid solution, and ultrasonication was used to make it uniformly dispersed. Chitosan was added and stirred for 2 h to prepare a first solution (a precursor solution of chitosan (30 mg / mL) and carbon nanozyme mixed);
[0101] Add glycyrrhizic acid (1.5 mg / mL) to the first solution and stir thoroughly until uniform to obtain a second solution;
[0102] Dissolving the thermosensitive agent β-glycerophosphate disodium pentahydrate in ultrapure water to obtain a third solution with a concentration of 2 g / mL;
[0103] The second solution and the third solution were mixed in a volume ratio of 3:1, stirred at 4°C until uniform, and finally the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel was obtained at 37°C.
[0104] The plate coating method was used to evaluate the in vitro antibacterial ability of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel. The specific experimental process is the same as Example 1. The antibacterial activity was compared by comparing the number of colonies. The number of methicillin-resistant Staphylococcus aureus colonies in the CS-β / C / GA group was reduced by 70.06% compared with the Control group, the number of colonies in the CS-β / C / GA+NIR group was reduced by 85.45% compared with the Control+NIR group, the number of MRSA colonies in the CS-β group was reduced by 9.89% compared with the control group, the number of MRSA colonies in the CS-β+NIR group was reduced by 9.56% compared with the control group, the number of MRSA colonies in the CS-β / C group was reduced by 40.76% compared with the control group, and the number of MRSA colonies in the CS-β / C+NIR group was reduced compared with the control group. 55.79%; the number of Pseudomonas aeruginosa colonies in the CS-β / C / GA group was reduced by 78.27% compared with the Control group, the number of colonies in the CS-β / C / GA+NIR group was reduced by 93.37% compared with the Control+NIR group, the number of PA colonies in the CS-β group was reduced by 10.36% compared with the control group, the number of PA colonies in the CS-β+NIR group was reduced by 9.98% compared with the control group, the number of PA colonies in the CS-β / C group was reduced by 28.28% compared with the control group, and the number of PA colonies in the CS-β / C+NIR group was reduced by 50.31% compared with the control group. It can be seen that the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel of the present invention exhibits a very significant synergistic antibacterial effect on both bacteria.
[0105] By constructing a complex infection live mouse model, the healing rate of mouse infected wounds of glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel was systematically investigated. The specific experimental process is the same as Example 1. On the 4th day, the wound healing speed of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group treated with near-infrared laser irradiation was slightly faster than that of the control group and the no-light group. The average wound healing rate of the CS-β / C / GA+NIR group was 57%, and the average wound healing rates of the Control+NIR group and CS-β / C / GA were 40% and 53%; on the 10th day, the wound of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel group treated with near-infrared laser irradiation was almost completely closed, which was significantly different from the other groups. The average wound healing rate of the CS-β / C / GA+NIR group was 89%, and the average wound healing rate of the Control+NIR group and CS-β / C / GA was 60% and 74%, showing a photothermal synergistic antibacterial and anti-inflammatory effect.
[0106] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel, characterized in that: The following steps are involved: Dispersing the carbon nanozyme in an acetic acid solution, performing ultrasonic dispersion, and adding chitosan to obtain a first solution; Adding glycyrrhizic acid to the first solution and stirring evenly to obtain a second solution; dissolving disodium β-glycerophosphate pentahydrate in water to obtain a third solution; The second solution and the third solution are mixed and stirred evenly to obtain a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel; The preparation method of the carbon nanozyme is as follows: Mix dimethylimidazole and methanol to obtain solution A; Mixing zinc nitrate hexahydrate with methanol to obtain solution B; Add the solution B into the solution A and stir evenly; The supernatant was discarded after centrifugation, and methanol was added to make the liquid level higher than the obtained solid. Ultrasonic dissolution was performed until there was no precipitation, and then centrifugation was performed again. This was one washing. After washing three times, the supernatant was discarded, vacuum dried, and then the obtained solid was ground and calcined to obtain the carbon nanozyme.
2. The method for preparing the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel according to claim 1, characterized in that: The mass volume ratio of dimethylimidazole to methanol is 3.24 g:100 mL; The mass volume ratio of the zinc nitrate hexahydrate to methanol is 2.94 g:100 mL; The speed of each centrifugation was 12000 rpm, and the time of each centrifugation was 10 min; The calcination temperature is 900° C., and the calcination time is 3 h.
3. The method for preparing the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel according to claim 1, characterized in that: The volume ratio of the second solution to the third solution is (3-10):
1.
4. The method for preparing the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel according to claim 3, characterized in that: The volume ratio of the second solution to the third solution is 3:1, 5:1 or 10:
1.
5. A glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 4.
6. Use of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel according to claim 5 in the preparation of antibacterial drugs.
7. Use of the glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel according to claim 5 in the preparation of a drug for promoting the healing of wounds infected with multiple bacteria.
Citation Information
Patent Citations
Preparation method and application of nano-composite natural polysaccharide hydrogel
CN117089085A
Injectable intelligent controlled-release hydrogel and application thereof in treatment of bone injury
CN117942427A